Possessivos de terceira pessoa na língua portuguesa nos séculos XIII e XIV - Patricia Fabiane Amaral da Cunha (2007)
This thesis analyses third person possessives. Based on data representing Medieval Portuguese, we investigate the implementation of dele and the variation among the different realizations of pronouns.Based on theoretical assumptions of the variationist sociolinguists (cf.LABOV, 1972, 1982, 1994, 2001), we demonstrate that the increasing of definite articles usage frequency, the decreasing of clitic possessives and the increasing of dele usage frequency would be concomitant.To explain the co-occurrence of these processes, we analyse the Dcategory based on Principles and Parameters Theory (cf. CHOMSKY, 1981, 1989, 1994). We argue that the competition between clitic possessives and definite articles for the same position would be related to the implementation of dele.